Ecuador’s Great Current Debt: The Sarayaku Case - Veintimilla Quezada, Silvia (2023)
The case of the Kichwa Sarayaku people vs. Ecuador is one of the most iconic and vindicatory of the Inter-American Human Rights System in rela-tion to the recognition of the violation of collective rights, specifically the right to prior, free, and informed consultation with indigenous peoples and communities on activities that put their lives or territories at risk. In this sense, the purpose of this research is to expose the contextual and legal reasons that led to this international dispute, in order to contribute to the legal debate that is unfolding around the incomplete compliance with the judgment issued by the Inter-American Court of Human Rights (IACHR) recognizing the international responsibility of the Ecuadorian State. For this purpose, a historical-political analysis of the background of the case has been developed in order to approach with a critical perspective the points of the sentence issued by the IACHR, which ten years after its issuance have still not been executed. The political, ideological, and economic preponderance dynamics have left aside elements inherent to the plurinational nature of the Ecuadorian State, such as the indigenous peoples ? worldview or nature as a guarantee for life. The Constitutional Court has the important responsibility of establishing a precedent on the application of internatio-nal standards on the protection of human rights, which fossil fuel compa-nies such as CGC (Compañía General de Combustibles) did not seem to have complied with.